Comprehensive Review of Temporomandibular Joint Disorders: Insights into Occlusal Splint Therapy, CBCT Diagnostics, and Upper Airway Dimensions - Amol Karagir; Amit Mhapuskar; Shridevi Adaki; Raghavendra Adaki; Manish Agrawal; Anirudha Shete (The Bioscan, 2024)
Temporomandibular joint disorders (TMJDs) are multifactorial conditions affecting the temporomandibular joint (TMJ), surrounding musculature, and associated structures. Myogenic TMJDs, characterized by muscular pain and dysfunction, are among the most prevalent subtypes. The management of TMJDs has increasingly focused on occlusal splints, which play a critical role in improving symptoms and modifying mandibular condylar positioning. This review explores the pathophysiology of TMJDs, the clinical features of myogenic disorders, and the role of occlusal splint therapy. It also delves into the relevance of mandibular condylar position, upper airway dimensions, and their interdependence with TMJD pathogenesis. Insights from key studies are discussed, emphasizing the need for advanced imaging modalities like cone-beam computed tomography (CBCT) in evaluating therapeutic outcomes. Furthermore, gaps in current research are highlighted, underscoring the need for comprehensive studies investigating long-term impacts of splint therapy on airway and TMJ function.